The Paris Arcades, the Ponte Vecchio and the Comma of Translation - Simon, Sherry (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractThis article argues that Canadian literary translation is enlarging its cultural and esthetic mandates. When Philip Stratford in the 1970s called translations of Quebec literature'news from the front,' he was referring to the journalistic role played by translators in transmitting Quebec literary news. Rather than acting exclusively as mediators, writer/ translators are now increasingly involved in creating hybrid literary texts informed by a double culture. The novels of Gail Scott, the 'renga' of Jacques Brault and E.D. Blodgett are examples of such texts. They use languages to cross traditions, making their texts a crossroads of sensibilities.